Computed tomography findings in senile dementia and normal aging. - Soininen, H (1982)
Computed tomography (CT) findings in 57 patients with senile dementia of Alzheimer type (SDAT), 19 patients with multi-infarct dementia and 85 controls of similar age and sex were studied. The SDAT patients differed from the controls of ventricular dilatation, frontal horn index, cella media index and the width of the third ventricle, and also in the index of cortical atrophy. Even the least severely demented SDAT patients differed from the controls. In the SDAT group with the increasing degree of intellectual impairment the ventricular dilatation increased, but cortical atrophy did not correlate with the psychological test score. The multi-infarct dementia patients differed from the controls in all CT variables including local changes. The SDAT patients had a more marked ventricular dilatation than the multi-infarct dementia patients. The multi-infarct dementia patients had more frequently local changes in SDAT patients. In the control group age correlated with ventricular dilatation, and the lower test scores correlated with cortical atrophy in the left temporal region.